A new species of Ternstroemia (Pentaphylacaceae) from La Amistad Binational Park and World Heritage Property, Costa Rica and Panama - Santamaria, Daniel Aguilar; Monro, Alex K; Jiménez-Madrigal, Quírico (Phytotaxa, 2015)
Ternstroemia amistadensis Q. Jiménez & D. Santam., a new tree species from La Amistad International Park in Costa Rica and Panama, is described and illustrated. Ternstroemia amistadensis is assessed as Near Threatened, It may be may be distinguished from other species in the genus based on its obovate, coriaceous and very shiny leaf laminae with obtuse-rounded apices and bearing many small black punctations below.